Analyzing the Requirement for Module-Based Reading Intervention for Children with Reading Difficulties in Sri Lanka - Safeek, N.M.M.; Hock, K.E.; Nachiappan, S. (International Journal of Academic Research in Progressive Education and Development, 2023)
Reading proficiency is a fundamental skill crucial for academic success. However, some children encounter reading difficulties stemming from decoding or linguistic comprehension challenges. This need analysis aims to identify the reading fluency module needs for junior secondary school students in Sri Lanka who have reading difficulties. The objectives are to find out the teachers' awareness of children with reading difficulties, to find out the teachers' perception of module needs for teaching reading to children with reading difficulties, and to find out the need for Smart Reading Module (SRM) development. An adapted questionnaire was used, involving 164 (59.8% female and 40.2% male) junior secondary teachers from the Puttalam South Division in Sri Lanka. SPSS version 29 facilitated robust data analysis. The surveyed teachers, 78.7% recognized reading difficulties as significant obstacles. A striking 93.9% supported teaching children with reading challenges, emphasizing the importance of reading fluency for academic success and the potential for effective intervention programs. Moreover, 85% found teaching reading to such children highly challenging. Additionally, 82.3% highlighted the necessity of a structured module for reading instruction. Furthermore, 90.9% advocated for Smart Reading Module (SRM) resources, including teacher guides with guidance and lesson plans for effective teaching.
Keywords: Need Analysis; Teaching Intervention; Children with Reading Difficulties; Sri Lanka